PENGARUH PERSEPSI SISWA TENTANG PROSES PEMBELAJARAN GEOGRAFI TERHADAP MINAT DAN HASIL BELAJAR DI SMA NEGERI 5 GORONTALO - Ismail, Rumiyati; Lihawa, Fitryane; Rusiyah, Rusiyah (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2024)
The purpose of this study is to examine: (1) The effect of students' perception about geography learning process on students' interest in learning at SMA Negeri 5 Gorontalo; (2) The effect of students' perception about geography learning process on students' learning outcomes in SMA Negeri 5 Gorontalo. The data collection method used is survey method. The subjects of this study were students of class XI and XII social studies of SMA Negeri 5 Gorontalo in the academic year 2023/2024 totaling 80 students. Data collection techniques used questionnaires and documentation. The research results obtained: (1) There is a significant influence between the variable of student perceptions of the learning process on the variable of student interest in learning, indicated by t value 6.186> t table 1.991 and Sig value. 0.000 < 0.05 (2) There is a significant influence between the variable of students' perception of the learning process on the variable of students' interest in learning, indicated by t value 2.456 > t table 1.991 and Sig value. 0.016 < 0.05, so it can be concluded that there is a significant influence between students' perceptions of the geography learning process on student interest and learning outcomes.